2019
DOI: 10.1080/19420862.2019.1605270
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroFcRn- dependent transcytosis assay as a screening tool for predictive assessment of nonspecific clearance of antibody therapeutics in humans

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles REPORT An in vitro FcRn-dependent transcytosis assay as a screening tool for predictive assessment of nonspecific clearance of antibody therapeutics in humans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 61 publications
(92 reference statements)
1
46
1
Order By: Relevance
“…However, despite these literature reports, the use of PBPK modeling for mAbs in the pharmaceutical industry is still limited. Most PBPK models published have relied on in vivo data for fitting as there have been few predictive in vitro assays described and few in vitro – in vivo relationships established . Although these models can fit the experimental data, the models are heterogeneous, and different groups have used not only different physiological parameters but also different representations of physiology to fit the data .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these literature reports, the use of PBPK modeling for mAbs in the pharmaceutical industry is still limited. Most PBPK models published have relied on in vivo data for fitting as there have been few predictive in vitro assays described and few in vitro – in vivo relationships established . Although these models can fit the experimental data, the models are heterogeneous, and different groups have used not only different physiological parameters but also different representations of physiology to fit the data .…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro – in vivo correlations of PK properties are therefore less well established. However, several physicochemical attributes, e.g., non‐specific charge‐based interactions, self‐association, and hFcRn binding affinity, have recently been shown to correlate with in vivo clearance (CL) . One particular in vitro assay is the affinity‐capture self‐interaction nanoparticle spectroscopy (AC‐SINS) assay .…”
mentioning
confidence: 99%
“…Previous work in this area has suggested that self-interactions and nonspecific interactions in phosphate-buffered saline or similar buffers may be important (27,28). Recently, assays based on cellular trafficking processes, facilitated by specific binding and transcytosis through the FcRn receptor, have been shown to be important in determining mAb PK (29). With respect to molecular attributes, PK modeling (30) and specific engineering of IgGs at the FcRn binding interface, between the C H 2 and C H 3 domains, have yielded definitive evidence of half-life extension or reduced clearance of mAbs in preclinical settings (31,32).…”
Section: No Pk Disadvantage For Selecting Mabs That Display Favorablementioning
confidence: 99%
“…The best-fit parameters were used to interpolate the viscosity at 150 mg/ml. In 11 cases (mAbs 6,11,13,14,22,24,28,29,41,53, and 57), the sample quantities available did not permit generation of the concentrationviscosity data. Instead, a single viscosity measurement was conducted on the sample at a target concentration of 150 mg/ml.…”
Section: Viscosity Measurementmentioning
confidence: 99%
“…A wide variety of in vitro assays have been used to evaluate nonspecific binding and antibody uptake, but none of these assays are able to quantitatively predict PK profiles 6 – 8 . In addition, cell-based assays such as FcRn-mediated transcytosis assays have been developed to predict the half-life of an antibody, but they can only be used to rank candidate antibodies by half-life 9 12 . For these reasons, an in vivo-based approach would be the most efficient strategy for evaluating the PK of an antibody not cleared by target-dependent elimination in animals and predicting it in humans.…”
Section: Introductionmentioning
confidence: 99%